GENETICS AND ECOLOGY OF Aedes spp. IN THE STATE OF MATO GROSSO - Cerqueira, Lenicy Lucas de Miranda; Butakka, Cristina Márcia de Menezes; Mariotto, Sandra; Miyazaki, Rosina Rosina Djunko (Seven Editora, 2024)
This chapter is a fundamental contribution to the understanding and management of one of the main vectors of diseases in Brazil. It is the result of a collaborative effort of a research group that has explored in depth the complex interaction between the genetics and ecology of Aedes spp., with a special focus on the specific conditions of the state of Mato Grosso – MT, Brazil. The analysis discusses the genetic diversity and ecological adaptations of Aedes spp., based on data collected directly in the territory of Mato Grosso. It presents studies from the last ten years, which reveal how environmental and genetic factors influence the population dynamics and vector capacity of these mosquitoes. First, it deals with the biology of the Aedes spp. mosquito, which makes a bibliographic review of the state of knowledge type in the time period from 2013 to 2023, on the subject in our state. It then discusses climate change and one health, in the face of arboviruses, and details the methods used to map the genetic diversity of Aedes spp. populations in Mato Grosso, aiming to clarify genetic variability and the possible implications for insecticide resistance and the spread of diseases. As future perspectives, the chapter also addresses the implications of the results obtained for future control and prevention strategies, discussing integrated approaches, including genomic studies, that can be adopted to mitigate the impacts of these diseases in the state, expanding knowledge about the vector.DOI: https://doi.org/10.56238/sevened2024.037-073